An approach based on consecutive high-speed counter-current chromatography for preparation of an active compound rutin from Apocynum venetum L. Issue 7 (9th May 2021) - Li, Haoquan; Cao, Zengyuan; Guo, Shuang; Gu, Dongyu; Wang, Shuai; Yang, Yi; He, Fei
Abstract: Apocynum venetum is a kind of plant with high medicinal value. Its main component is rutin, which is widely used. In the present study, an efficient method based on high-speed counter-current chromatography (HSCCC) was established to separate rutin from A. venetum . The optimized solvent system composed of ethyl acetate- n -butanol-water (4:1:5, v/v ) was selected for HSCCC separation. It was found that the maximum loading amount was 1 g, but the loading amount did not affect the two-phase equilibrium of solvent system. Therefore, consecutive high-speed counter-current chromatography was introduced to further improve the yield in the present study. As a result, 292 mg of rutin with 95% purity was obtained from 2.4 g crude sample. The retention of the stationary phase was 27%, which was almost unchanged. The current strategy can not only be used for the scale-up preparation of rutin, but also provide an example for the preparation of other natural active compounds. Graphical abstract: UF0001